Association of the severity and pattern of pituitary adenoma-related headache with the size and type of adenoma - Farzad Najafipour; Newsha Hedayati; Neda Hedayati; Mehdi Farhoudi (Journal of Preventive Epidemiology, 2024)
Introduction: Headache is one of the essential symptoms of pituitary adenoma associated with the tumor and the patient’s characteristics. The pattern of adenoma-related headaches varies widely and can significantly impact the patient’s quality of life. Objectives: We aimed to investigate the severity and pattern of headaches in patients with pituitary adenoma in Iran. Patients and Methods: In this cross-sectional study, we investigated 109 patients with an initial complement of headaches. The diagnosis of pituitary adenoma was confirmed. Patients’ demographic characteristics [e.g., gender, body mass index (BMI), and age] and tumor characteristics (e.g., subtype of tumor and size of tumor) were collected by interview, clinical examination, and imaging. We measured the severity of the headache using Headache Impact Test-6 (HIT-6) questionnaire version 1.1. Results: In our study, the most common subtype of pituitary adenoma was prolactinoma, followed by non-functional growth hormone (GH)-releasing and adrenocorticotropic hormone (ACTH)-releasing adenomas. Functional adenoma was significantly more common in women; however, the incidence of non-functional adenoma was more in men (61%), indicating the correlation between gender and subtype of adenoma (P=0.008). Most tumors were functional microadenomas (69%), while macroadenomas were primarily non-functional (50%). The HIT-6 scores demonstrated that functional microadenomas had higher HIT-6 scores and patients with prolactinoma experienced more severe headaches than other subtypes (P=0.003). Conclusion: Our study revealed significant effects of the type of adenoma on the severity of headaches, as patients with functional microadenomas had more muscular headaches. Additionally, the hormone-releasing function of tumors plays a vital part in the advent and severity of adenoma-related headaches.